EXPLORATION OF HIDROCARBONS IN A BOUNDARY AREA TO THE KARIPUNA TERRITORY: EXTRACTIVE DEVELOPMENTISM, INDIGENOUS KNOWLEDGE AND STATE PREDATION IN THE GUIANE AMAZON IN THE 21 ST CENTURY (Social and Environmental Law Journal, 2023)
The article takes a nuanced analysis of the exploratory research process aiming at the international auction of oil and gas extraction blocks in an area bordering the Uaçá Indigenous Territory, in the Cabo Orange region, current municipality of Oiapoque/Amapá/Brazil, between the years of 2012 to 2018. On the occasion, students and leaders of the Karipuna People pointed out inconsistencies in the environmental impact studies presented to the Brazilian agency responsible for licensing; as well as supposed meetings and hearings for consultation and clarification on the extraction process. The traditional knowledge proposed by Karipuna elders and young academics considered characteristics of the behavior of the fluvial-maritime currents in the region that apparently were not covered in the EIA-RIMA, which can give rise to an interesting debate on the relationship between ethnosabers and scientific knowledge, such as as expressed by contract oceanography. The combination of the reports and the failure of the exploratory process on the coast of Amapá allows us to relate the resistance of the natives, in the face of the historical extractive violence operated by different Latin American states, as a rule, to the detriment of the socio-environmental rights of their peoples and traditional populations.
Keywords: Uaçá Indigenous Land; Oil and Gas in the Amazon; Karipuna People